First Report of Root Knot (Meloidogyne incognita) on Okra (Abelmoschus esculentus (L) moench) in Dang District of Gujarat - Prajapati, V. P.; Singh, Pushpendra; Deshmukh, A. J. (International Journal of Economic Plants, 2018)
Root knot nematode was heavily infested on okra crop in farmer’s field of Kudkas village in Dang district of Gujarat state. Identification of the Meloidogyne incognita is the first occurrence on okra from dang district of Gujarat.